Penerapan Metode Extreme Programming Pada Aplikasi Monitoring Kegiatan Karang Taruna Sangiang Jaya Berbasis Android - Nur Santi Dewi; Jaka Sutresna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Abstract− The development of technology has progressed very rapidly from various kinds of existing technological, devolopments, one of which is information and communication tecnology. Information technology is widely used as a monitoring medium for various activities. E-monitoring is a term for the application of technology to the (electronic) reporting system. Mobile Apps-based tecnology is an application created for mobile devices such as smartphones, smartwatches, tablets, and others. One of the mobile operating system used by smartpohenes id Android. This Android-based monitoring system for Karang Taruna activities is very much needed by Karang Taruna members, residents and teh Sangiang Jaya Village, Tangerang City. The result of this research is the application of the Extreme Programming Method for monitroing Karang Taruna Sangiang Jaya activities based on Android. If previously residents did not know inrmation abou existing activities, and the Kelurahan dis not know the extent of the coral activities carried out by Karang Taruba, then with this system they only need to open it on smartphones. It is hoped that with this monitoring system, it can be useful for the community and all related parties. In related parties. In this monitoring system, teh community can find out information on activities at the Yout Organization and the Kleurahan can find out the percentage of existing activities. The method used in making this monitoring system is the Extreme Programming method. . Keywords: Monitoring System, Android, Karang Taruna, Extreme Programming